Polishing composition suitable for chemical mechanical polishing of copper interconnection structure of integrated circuit and application of polishing composition

By introducing star-shaped polyethylene glycol polymers into a chemical mechanical polishing slurry to form a two-dimensional polymer network, the problem of copper polishing depressions in copper interconnect structures is solved, achieving efficient copper removal and good surface uniformity.

CN119264816APending Publication Date: 2025-01-07WANHUA CHEM GRP ELECTRONIC MATERIALS CO LTD +1

Patent Information

Application Number
CN202310809308.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing chemical mechanical polishing slurries suffer from copper polishing depressions in copper interconnect structures, making it difficult to achieve efficient copper removal while maintaining good surface uniformity and low depression.

Method used

A polishing composition comprising abrasive particles, oxidant, complexing agent, corrosion inhibitor, star-shaped polyethylene glycol polymer, pH adjuster and deionized water is used. The star-shaped polyethylene glycol polymer forms a two-dimensional polymer network on the wafer surface, balancing pressure inhomogeneity and reducing indentation.

Benefits of technology

High-speed copper removal was achieved, resulting in reduced surface depressions after polishing, good wafer surface uniformity, and improved flatness of the copper interconnect structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004319040300000031
    Figure BDA0004319040300000031
  • Figure BDA0004319040300000032
    Figure BDA0004319040300000032
  • Figure BDA0004319040300000061
    Figure BDA0004319040300000061
Patent Text Reader

Abstract

The invention discloses a polishing composition suitable for chemical mechanical polishing of a copper interconnection structure of an integrated circuit and application of the polishing composition. The chemical mechanical polishing composition comprises grinding particles, an oxidizing agent, a complexing agent, a corrosion inhibitor, a star-shaped polyethylene glycol polymer, a pH regulator, an optional nonionic polymer and deionized water. The star-shaped polyethylene glycol polymer in the polishing composition disclosed by the invention can act on the surface of a polished material, so that the polishing depression of a metal interconnection structure is reduced, and the in-chip heterogeneity of the polished surface is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical mechanical polishing, and in particular to a polishing composition suitable for chemical mechanical polishing of copper interconnection structures of integrated circuits and application thereof. Technical Background

[0002] The demand for smaller chip size and higher computing / storage capacity can be achieved by reducing line width and increasing the number of stacking layers, which requires good flatness between chip layers. Currently, the only technology to achieve good inter-layer flatness in chip manufacturing is chemical mechanical polishing (CMP).

[0003] Copper has been widely used as a wiring metal in integrated circuit manufacturing instead of aluminum, mainly due to the advantages of Cu wiring, such as lower resistivity and RC delay, better resistance to electromigration, etc. The dual Damascene process is used to make copper wiring layers. The general steps are as follows: first, a groove is etched on the dielectric layer; then a copper barrier layer, such as Ta / TaN, is filled in the groove. In order to improve the adhesion between copper and the groove, a copper seed layer is deposited; finally, the groove is filled with copper using electroplating; finally, CMP of the copper wiring layer is performed.

[0004] The copper wiring layer CMP process is mainly divided into three steps: the first step is to use copper polishing liquid to quickly remove a large amount of copper under high polishing pressure; the second step is to use copper polishing liquid to remove the remaining copper and stop at the barrier layer under low polishing pressure; the third step is to use barrier layer polishing liquid to remove barrier layer metal, dielectric layer and a small amount of copper layer. The second step of polishing needs to stop on the barrier layer and try not to reduce the depth of the copper wiring in the dielectric layer groove. This requires the copper polishing liquid to have a low removal rate for the dielectric layer. In other words, the copper polishing liquid is required to have a high selectivity for the dielectric layer and copper. This characteristic of the copper polishing liquid causes a depression on the surface of the dielectric layer medium and the copper medium after the second step of polishing. Another depression comes from the excessive polishing of the dielectric layer between the wiring metal by CMP. The generation of depressions leads to a reduction in the width of the copper wiring and an increase in resistivity.

[0005] Invention patent CN1939995B proposes that the use of compounds with an imidazole skeleton or an isothiazolin-3-one skeleton can reduce copper polishing depressions. Such substances can be used as copper corrosion inhibitors and can improve the surface quality of copper after polishing, but the effect of reducing depressions is not obvious. Patent JPA2006179845 discloses an organic acid with a specific structure, which can significantly improve the removal of copper, but will cause severe copper corrosion and the reduction of depressions is not obvious. Invention patent CN101240146A discloses a combination of a specific amino acid and a nitrogen-containing heterocyclic compound, which can obtain a high copper removal rate and a low roughness of the copper surface after polishing, but the effect of improving depressions is not enough. Invention patent CN101186784A discloses an α-amino acid, a benzotriazole derivative, and a special surfactant combination, which obtains a good removal rate and has a very low depression depth, but the pH value required by the compound is 9-11, which is not conducive to obtaining a good surface uniformity after polishing. Invention patent CN100536081C discloses a composition containing benzotriazole derivatives and polyoxyethylene alkyl ether acetate or polyoxyethylene alkyl ether phenol ether phosphate, which composition is difficult to obtain a high copper removal rate. Therefore, it is still necessary to improve the polishing liquid components from the perspective of chemical formula to overcome the various drawbacks of the aforementioned prior art. Summary of the invention

[0006] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a polishing composition suitable for chemical mechanical polishing of integrated circuit copper interconnect structures, which can achieve high-speed removal of copper and has low surface depression and good intra-chip non-uniformity after polishing.

[0007] Another object of the present invention is to provide the application of the polishing composition suitable for chemical mechanical polishing of copper interconnection structures of integrated circuits in chemical mechanical polishing.

[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0009] A polishing composition suitable for chemical mechanical polishing of copper interconnection structures of integrated circuits comprises abrasive particles, an oxidizing agent, a complexing agent, a corrosion inhibitor, a star-shaped polyethylene glycol polymer, a pH regulator, an optional non-ionic polymer and deionized water.

[0010] In a preferred embodiment, the mass percentage of the components of the polishing composition is: 0.01wt%-0.5wt% of abrasive particles, 0.1wt%-5wt% of oxidizing agent, 0.1wt%-5wt% of complexing agent, 0.01wt%-0.1wt% of corrosion inhibitor, 0.001wt%-0.1wt% of star-shaped polyethylene glycol polymer, 0.01wt%-1wt% of pH adjusting agent, 0%-0.1wt% of non-ionic polymer, and the balance is deionized water.

[0011] In a specific embodiment, the star-shaped polyethylene glycol polymer has the general structural formula of formula (1) or formula (2):

[0012]

[0013] wherein m is an integer of 20-200, preferably 50; R1 is independently selected from any one of H, amino, thiol, maleimide, methacrylic acid, and acrylamide, preferably H;

[0014]

[0015] Wherein, n is an integer from 0 to 4, and R2 is Wherein, p is an integer of 20-200, preferably 50.

[0016] In a specific embodiment, the star-shaped polyethylene glycol polymer is selected from 4-arm star-polyethylene glycol (4arm-PEG), 5-arm star-polyethylene glycol-hydroxyl (5arm-PEG-OH), 8-arm star-polyethylene glycol-hydroxyl (8arm-PEG-OH), 4-arm star-polyethylene glycol-thiol (4arm-PEG-SH), 4-arm star-polyethylene glycol-amino (4arm-PEG-NH2), 4-arm star-polyethylene glycol-acrylate (4arm-PEG-AC), 4-arm star-polyethylene glycol-acrylamide (4arm-PEG-ACA), preferably 4arm-PEG.

[0017] In a specific embodiment, the abrasive particles are selected from one or more of silicon oxide, zirconium oxide, cerium oxide, aluminum oxide, and silicon carbide particles; preferably, the abrasive particles are silicon oxide; more preferably, the silicon oxide abrasive particles are silica sol prepared by any one of the methods of elemental silicon method, ion exchange method, and sol-gel method, preferably sol-gel silica sol.

[0018] In a preferred embodiment, the size of the abrasive particles is 10-300 nm, preferably 40-120 nm.

[0019] In a specific embodiment, the silicon oxide abrasive particles may be spherical or non-spherical with an association degree of 2-4, preferably non-spherical particles.

[0020] In a specific embodiment, the oxidizing agent is hydrogen peroxide.

[0021] In a specific embodiment, the complexing agent is selected from one or more of glycine, malonic acid, lysine, serine, citric acid, oxalic acid, valine, alanine, threonine, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, dipotassium ethylenediaminetetraacetate, nitrile triacetic acid, ethylenediaminetetramethylenephosphonic acid, sodium ethylenediaminetetramethylenephosphate, and aminotrimethylenephosphonic acid, preferably any one of glycine, citric acid, and ethylenediaminetetraacetic acid, and more preferably citric acid or glycine.

[0022] In a specific embodiment, the corrosion inhibitor is selected from at least any one of aspartic acid, glutamic acid, cysteine, tetrazole, 2-amino-pyrrole, pyrazole, imidazole, 1,2,4-triazole, 3-amino-1,2,4-triazole, benzotriazole, cytosine, uracil, and 2-methyl-4-isothiazolinetrione, preferably any one of aspartic acid, 1,2,4-triazole, or 2-methyl-4-isothiazolinetrione.

[0023] In a specific embodiment, the pH adjuster is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, ethanolamine, diethanolamine, triethanolamine, aniline, potassium hydroxide, sodium hydroxide, guanidine compounds, and alkali metal alkoxides, preferably any one of tetramethylammonium hydroxide, ethanolamine, potassium hydroxide, and guanidine carbonate, and more preferably tetramethylammonium hydroxide, ethanolamine, or potassium hydroxide.

[0024] In a preferred embodiment, the pH value of the polishing composition is 3-10, preferably 4-9, more preferably 5-8.

[0025] In a specific embodiment, the nonionic polymer is selected from at least any one of polyethylene glycol, polyvinyl pyrrolidone, polyacrylamide, acrylic acid-acrylate copolymer, diblock or triblock copolymer of polyoxyethylene and polyoxypropylene; preferably, the molecular weight of the nonionic polymer is 200-1000000, preferably 400-100000.

[0026] On the other hand, the aforementioned polishing composition suitable for chemical mechanical polishing of copper interconnect structures of integrated circuits is used in chemical mechanical polishing of copper interconnect structures in integrated circuit manufacturing.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The star-shaped polyethylene glycol polymer of the present invention has a nonlinear structure. During the polishing process, the polymer molecules are adsorbed on the surface of the wafer and arranged in two dimensions, forming a polymer network on the surface of the wafer, which is conducive to reducing the amount of depression. Limited by mechanical control, the pressure applied to the wafer during the polishing process is uneven. Compared with linear polymers, the two-dimensionally arranged polymer layer formed by the star-shaped polyethylene glycol on the wafer can better balance the unevenness of the pressure, thereby achieving good uniformity of the polished wafer. DETAILED DESCRIPTION

[0029] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.

[0030] A polishing composition suitable for chemical mechanical polishing of copper interconnection structures of integrated circuits, wherein the mass percentage of each component is: 0.01wt%-0.5wt% of abrasive particles, 0.1wt%-5wt% of an oxidant, 0.1wt%-5wt% of a complexing agent, 0.01wt%-0.1wt% of a corrosion inhibitor, 0.001wt%-0.1wt% of a star-shaped polyethylene glycol polymer, 0.01wt%-1wt% of a pH regulator, 0%-0.1wt% of a non-ionic polymer, and the balance is deionized water.

[0031] In another preferred embodiment, the mass percentage of each component is: 0.01wt%-0.5wt% of abrasive particles, 0.1wt%-5wt% of oxidant, 0.1wt%-5wt% of complexing agent, 0.01wt%-0.1wt% of corrosion inhibitor, 0.001wt%-0.1wt% of star-shaped polyethylene glycol polymer, 0.01wt%-1wt% of pH adjuster, 0.001%-0.1wt% of non-ionic polymer, and the balance is deionized water.

[0032] The general structure of the star-shaped polyethylene glycol polymer is formula (1):

[0033]

[0034] wherein m is 20-200, such as 20, 30, 40, 50, 60, 70, 80, 90, 100, 120, 150, 180, 200, etc., preferably 50; and R1 is selected from any one of H, amino, thiol, acrylamide, maleimide, methacrylic acid, and acrylamide, preferably H.

[0035] The general structure of the star-shaped polyethylene glycol polymer may also be formula (2):

[0036]

[0037] Wherein, n is an integer of 0-4, such as 0, 1, 2, 3, 4, and R2 is Wherein, p is an integer of 20-200, for example, 20, 30, 40, 50, 60, 70, 80, 90, 100, 120, 150, 180, 200, etc., and preferably 50.

[0038] Specifically, the star-shaped polyethylene glycol polymer is selected from 4-arm star-polyethylene glycol (4arm-PEG), 5-arm star-polyethylene glycol-hydroxyl (5arm-PEG-OH), 8-arm star-polyethylene glycol-hydroxyl (8arm-PEG-OH), 4-arm star-polyethylene glycol-thiol (4arm-PEG-SH), 4-arm star-polyethylene glycol-amino (4arm-PEG-NH2), 4-arm star-polyethylene glycol-acrylate (4arm-PEG-AC), 4-arm star-polyethylene glycol-acrylamide (4arm-PEG-ACA), preferably 4arm-PEG.

[0039] As the star-shaped polyethylene glycol polymer is a nonlinear structure, during the polishing process, the polymer molecules are adsorbed on the surface of the wafer and arranged in two dimensions, forming a polymer network on the surface of the wafer, which is conducive to reducing the amount of depression. Limited by mechanical control, the pressure applied to the wafer during the polishing process is uneven. Compared with linear polymers, the two-dimensional arrangement polymer layer formed by the star-shaped polyethylene glycol on the wafer can better balance the unevenness of the pressure, thereby achieving good uniformity of the polished wafer. The amount of the polymer added is 0.001wt%-0.1wt% of the mass of the polishing composition, for example, including but not limited to 0.001wt%, 0.003wt%, 0.005wt%, 0.008wt%, 0.01wt%, 0.02wt%, 0.03wt%, 0.04wt%, 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.1wt%. The content of the polymer should not be too high, otherwise the rheological properties of the polishing liquid will be affected, while if it is too low, the effect described in the present invention cannot be achieved.

[0040] The abrasive particles are selected from any one of silicon oxide, zirconium oxide, cerium oxide, aluminum oxide, and silicon carbide, preferably silicon oxide abrasive particles. There is no particular restriction on the preparation method of the silicon oxide abrasive particles, such as any one of a single silicon method, an ion exchange method, and a sol-gel method. The silicon oxide abrasive particles can be spherical or non-spherical with a degree of association of 2-4, preferably non-spherical particles. There is no restriction, and the specific preparation method can refer to the prior art, or the corresponding abrasive can be directly purchased on the market. In addition, the size of the abrasive particles is 10-300nm, including but not limited to 20nm, 50nm, 75nm, 100nm, 120nm, 150nm, 180nm, 200nm, 230nm, 250nm, 270nm, 285nm, 300nm, preferably 40-120nm. The amount of abrasive particles added is 0.01wt%-0.5wt% of the mass of the polishing composition, for example including but not limited to 0.01wt%, 0.02wt%, 0.03wt%, 0.04wt%, 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% and the like.

[0041] The pH adjuster is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, ethanolamine, diethanolamine, triethanolamine, aniline, potassium hydroxide, sodium hydroxide, guanidine compounds, and alkali metal alkoxides, preferably any one of tetramethylammonium hydroxide, ethanolamine, potassium hydroxide, and guanidine carbonate, and more preferably tetramethylammonium hydroxide, ethanolamine, and potassium hydroxide.

[0042] The pH adjuster is added in an amount of 0.01wt%-1wt% of the mass of the polishing composition. Specifically, the pH value of the polishing composition is adjusted to 4-9 by the pH adjuster, for example, including but not limited to 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9. Preferably, the pH value of the polishing composition is adjusted to 5-8. The polishing composition within this pH range is more suitable for copper polishing process.

[0043] As the complexing agent, it is selected from one or more of glycine, malonic acid, lysine, serine, citric acid, oxalic acid, valine, alanine, threonine, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetic acid, dipotassium ethylenediaminetetraacetic acid, nitrile triacetic acid, ethylenediaminetetramethylenephosphonic acid, sodium ethylenediaminetetramethylenephosphate, and aminotrimethylenephosphonic acid, preferably any one of glycine, citric acid, and ethylenediaminetetraacetic acid, and more preferably citric acid or glycine. The amount of the complexing agent added is 0.1wt%-5wt% of the mass of the polishing composition, for example, including but not limited to 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, and 5wt%. The addition of the complexing agent in the polishing composition is conducive to complexing the free metal ions in the polishing liquid and promoting the removal of copper. Adding too much will lead to an increase in the roughness of the polishing surface, and adding too little will not reach the required copper removal rate.

[0044] The corrosion inhibitor is selected from any one of aspartic acid, glutamic acid, cysteine, tetrazole, 2-amino-pyrrole, pyrazole, imidazole, 1,2,4-triazole, 3-amino-1,2,4-triazole, benzotriazole, cytosine, uracil, 2-methyl-4-isothiazoline trione, preferably any one of aspartic acid, 1,2,4-triazole, and 2-methyl-4-isothiazoline trione. The amount of the corrosion inhibitor added is 0.01wt%-0.1wt% of the mass of the polishing composition, for example, including but not limited to 0.01wt%, 0.02wt%, 0.04wt%, 0.06wt%, 0.08wt%, 0.1wt%. The addition of the corrosion inhibitor in the polishing composition can form a protective film with the copper surface and reduce the roughness of the copper surface after polishing. Adding too much will result in a too low copper removal rate, and adding too little will not achieve the effect of protecting the copper surface from chemical corrosion.

[0045] The oxidant is hydrogen peroxide. Hydrogen peroxide first oxidizes copper into CuO / Cu2O to form a softened copper oxide film, which is removed by mechanical action and the complexing action of the complexing agent. The amount of the oxidant added is 0.1wt%-5wt% of the mass of the polishing composition, for example, including but not limited to 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%. If too little hydrogen peroxide is added, not only the required copper removal rate cannot be achieved, but also the copper surface roughness after polishing is high, and too much addition will inhibit the copper removal rate.

[0046] The polishing composition of the present invention may optionally contain a nonionic polymer in an amount of 0% to 0.1 wt%, preferably 0.001 wt% to 0.1 wt%. The nonionic polymer is selected from at least one of polyethylene glycol, polyvinyl pyrrolidone, polyacrylamide, acrylic acid-acrylate copolymer, diblock or triblock copolymer of polyoxyethylene and polyoxypropylene, such as polyethylene glycol or polyvinyl pyrrolidone; preferably, the molecular weight of the nonionic polymer is 200 to 1,000,000, such as 200, 500, 1,000, 5000, 10,000, 50000, 100,000, 1,000,000, etc., preferably 400 to 100,000.

[0047] The present invention is further explained below by more specific examples, but does not constitute any limitation.

[0048] Polishing liquid preparation

[0049]

[0050] Mix the substances in the table evenly, make up the balance in the formula with deionized water, and adjust the pH to 7 with potassium hydroxide.

[0051] After the above substances are mixed uniformly, 1 wt % of hydrogen peroxide is added thereto and mixed uniformly to obtain a sample for polishing.

[0052] In order to reduce the experimental error caused by the decomposition of hydrogen peroxide over time, the samples were used within 3 hours after preparation.

[0053] Polishing rate evaluation

[0054] In the following examples, the instruments and parameters used during copper polishing are as follows:

[0055]

[0056] In the following embodiments, the copper wafer used for polishing is a 50000A copper film electroplated on a 500-micron single crystal silicon substrate, and the size of the copper wafer is 12 inches.

[0057] On the diameter of a 12-inch wafer, take the zero point as the starting point, select a point every 1 cm in the positive and negative directions, and take a total of 28 points. Use a four-probe conductivity meter to test the conductivity of the points in the selected area on the copper wafer, so as to calculate the thickness of the copper wafer. The difference in thickness of the copper wafer before and after polishing divided by the polishing time is the polishing rate of copper.

[0058] Wafer uniformity evaluation after polishing

[0059] The intra-wafer non-uniformity (NU) parameter is used to evaluate the uniformity of the wafer after polishing. The smaller the NU, the better the flatness of the wafer. The NU calculation formula is as follows:

[0060]

[0061] n is the number of points tested, Xi is the polishing rate corresponding to each point tested, and X is the average polishing rate.

[0062] Evaluation of polishing depression

[0063] Preparation method of polished wafer: First, a groove is etched on the silicon oxide layer, the width of the groove is 0.01-50μm and the depth is 500nm. A 30nm thick TaN film is prepared on the patterned wafer by sputtering, followed by a 50nm thick copper film by sputtering, and finally a 10000A thick copper film is prepared by electroplating. Polished wafers can be processed and manufactured by CMP consumables manufacturers.

[0064] Polishing conditions: The polishing pressure was 1 psi, and the other conditions were the same as the polishing rate evaluation method.

[0065] The test method for the depression of the graphic wafer is as follows: Use a step meter to measure in the order of dielectric layer-copper wire depression-dielectric layer. The height difference between the dielectric layer surface and the lowest point of the depression is the depression.

[0066] Other materials, instruments and reagents in the examples and comparative examples of the present invention were purchased from commercial sources. The polymer of the general structural formula (1) was purchased from Xiamen Sinobond Biotechnology Co., Ltd., and the polymer of the general structural formula (2) was purchased from Laysan Bio.

[0067] Example

[0068] The types and contents of the substances added to the polishing liquid formulas used in the embodiments and comparative examples are shown in Table 1, and the balance is deionized water.

[0069] The polishing performance of the polishing liquids used in the embodiments and comparative examples was tested according to the aforementioned method. The results are shown in Table 2.

[0070] Table 1 Material ratio of examples and comparative examples

[0071]

[0072] Table 2 Comparison of polishing performance test data of embodiments and comparative examples

[0073]

[0074]

[0075] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A polishing composition suitable for chemical mechanical polishing of integrated circuit copper interconnect structures, characterized in that: comprising abrasive particles, an oxidizing agent, a complexing agent, a corrosion inhibitor, a star-shaped polyethylene glycol polymer, a pH adjusting agent, an optional nonionic polymer, and deionized water; Preferably, the mass percentage of each component of the polishing composition is: 0.01wt%-0.5wt% of abrasive particles, 0.1wt%-5wt% of oxidant, 0.1wt%-5wt% of complexing agent, 0.01wt%-0.1wt% of corrosion inhibitor, 0.001wt%-0.1wt% of star-shaped polyethylene glycol polymer, 0.01wt%-1wt% of pH adjuster, 0%-0.1wt% of non-ionic polymer, and the balance is deionized water.

2. The polishing composition according to claim 1, characterized in that The general structural formula of the star-shaped polyethylene glycol polymer is formula (1) or formula (2): wherein m is an integer of 20-200, preferably 50; R1 is independently selected from any one of H, amino, thiol, maleimide, methacrylic acid, and acrylamide, preferably H; Wherein, n is an integer from 0 to 4, and R2 is Wherein, p is an integer of 20-200, preferably 50.

3. The polishing composition according to claim 2, characterized in that The star-shaped polyethylene glycol polymer is selected from any one of 4-arm star-shaped polyethylene glycol (4arm-PEG), 5-arm star-shaped polyethylene glycol-hydroxyl (5arm-PEG-OH), 8-arm star-shaped polyethylene glycol-hydroxyl (8arm-PEG-OH), 4-arm star-shaped polyethylene glycol-thiol (4arm-PEG-SH), 4-arm star-shaped polyethylene glycol-amino (4arm-PEG-NH2), 4-arm star-shaped polyethylene glycol-acrylate (4arm-PEG-AC), and 4-arm star-shaped polyethylene glycol-acrylamide (4arm-PEG-ACA), preferably 4arm-PEG.

4. The polishing composition according to claim 1, characterized in that The abrasive particles are selected from one or more of silicon oxide, zirconium oxide, cerium oxide, aluminum oxide, and silicon carbide particles; preferably, the abrasive particles are silicon oxide; more preferably, the silicon oxide abrasive particles are silica sol prepared by any one of a single silicon method, an ion exchange method, and a sol-gel method, preferably a sol-gel method silica sol; Preferably, the size of the abrasive particles is 10-300 nm, preferably 40-120 nm; Preferably, the silicon oxide abrasive particles are spherical particles, or non-spherical particles with an association degree of 2-4, preferably non-spherical particles with an association degree of 2-4.

5. The polishing composition according to claim 1, characterized in that The oxidant is hydrogen peroxide.

6. The polishing composition according to claim 1, characterized in that The complexing agent is selected from one or more of glycine, malonic acid, lysine, serine, citric acid, oxalic acid, valine, alanine, threonine, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, dipotassium ethylenediaminetetraacetate, nitrile triacetic acid, ethylenediaminetetramethylenephosphonic acid, sodium ethylenediaminetetramethylenephosphate, and aminotrimethylenephosphonic acid, preferably any one of glycine, citric acid, and ethylenediaminetetraacetic acid, more preferably citric acid or glycine.

7. The polishing composition according to claim 1, characterized in that The corrosion inhibitor is selected from at least any one of aspartic acid, glutamic acid, cysteine, tetrazole, 2-amino-pyrrole, pyrazole, imidazole, 1,2,4-triazole, 3-amino-1,2,4-triazole, benzotriazole, cytosine, uracil, and 2-methyl-4-isothiazolinetrione, preferably any one of aspartic acid, 1,2,4-triazole, or 2-methyl-4-isothiazolinetrione.

8. The polishing composition according to claim 1, characterized in that The pH regulator is selected from one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, ethanolamine, diethanolamine, triethanolamine, aniline, potassium hydroxide, sodium hydroxide, guanidine compounds, and alkali metal alkoxides, preferably any one of tetramethylammonium hydroxide, ethanolamine, potassium hydroxide, and guanidine carbonate, and more preferably tetramethylammonium hydroxide, ethanolamine, or potassium hydroxide; Preferably, the pH value of the polishing composition is 3-10, preferably 4-9.

9. The polishing composition according to claim 1, characterized in that The nonionic polymer is selected from at least any one of polyethylene glycol, polyvinyl pyrrolidone, polyacrylamide, acrylic acid-acrylate copolymer, diblock or triblock copolymer of polyoxyethylene and polyoxypropylene; preferably, the molecular weight of the nonionic polymer is 200-1000000, preferably 400-100000.

10. Use of the polishing composition suitable for chemical mechanical polishing of copper interconnect structures of integrated circuits according to any one of claims 1 to 9 in chemical mechanical polishing of copper interconnect structures in integrated circuit manufacturing.

Citation Information

Patent Citations

  • Polishing composition

    CN100536081C

  • Polishing composition

    CN101186784A

  • Metal-polishing composition and chemical mechanical polishing method by using the same

    CN101240146A

  • Aqueous polishing liquid and chemical mechanical polishing method

    CN1939995B

Cited By

  • Polishing composition and application thereof

    CN120365857A